Dark adaptation changes in highly myopic patients. Issue 3 (May 2019) - Messerlin, Arnaud; Greth, Mathieu; Bourcier, Tristan; Sauer, Arnaud; Speeg-Schatz, Claude; Gaucher, David
Purpose: The objective of this study was to determine whether the dark adaptation time was longer in highly myopic patients than in emmetropic patients and whether there was a correlation between dark adaptation results and axial length. Patients and methods: We conducted a retrospective study that included highly myopic patients with −6.00 dioptres or more, matched to emmetropic control patients of the same age. All patients underwent an automated adaptometry protocol that calculates the rod intercept that reflects rod-mediated dark adaptation. Axial length was measured. Colour photographs were taken to look for retinal atrophic lesions. Results: A total of 25 highly myopic patients and 25 control patients were included. The mean rod intercept was 4.38 (±1.60) min in the myopic patients and 4.27 (±1.41) min in the control patients. This difference was not statistically significant ( p  = 0.79). However, in myopic patients, the longer the axial length was, the longer the dark adaptation time was ( p  = 0.0003). In addition, dark adaptation was significantly longer in myopic patients with retinal pigment epithelium atrophy than in patients without lesions ( p  = 0.0398). Conclusion: In this study, dark adaptation time did not significantly differ between myopic patients and controls but was correlated with axial length in patients with severe myopia and was significantly longer in the presence of retinal pigment epithelium atrophic lesions.